Going viral: Inflation narratives and the macroeconomy - Max Weinig; Ulrich Fritsche (Universität Hamburg, Fakultät für Wirtschafts- und Sozialwissenschaften, WiSo-Forschungslabor, 2024)
In recent years, there has been increasing interest in the analysis of narratives in macroeconomic research. Our paper contributes to this research by proposing a way to identify and extract economic narratives from media reports. Therefore, this paper applies state-of-the-art bag-of-words text analysis methods to a large news corpus covering five years of news coverage in combination with results from a survey study on recent inflation narratives (Andre et al., 2023) in the US. This approach enables us to measure the prevalence and spread of inflation narratives over time and to examine the role of these narratives in aggregate macroeconomic expectations. Using Granger causality tests and local projections, we provide empirical evidence on the dynamics between inflation narratives and inflation expectations. Moreover, the paper highlights the vast heterogeneity across shortterm and mid-term inflation expectations as well as socioeconomic groups.
Keywords: D84; E31; E32; E52; E71; 330; narratives; expectations; inflation; media; textual data; machine learning